2018
DOI: 10.1016/j.celrep.2018.05.084
|View full text |Cite
|
Sign up to set email alerts
|

The PARP1-Siah1 Axis Controls HIV-1 Transcription and Expression of Siah1 Substrates

Abstract: SUMMARY Recentstudieshave revealeda keyrole ofPARP1that catalyzes the poly-ADP-ribosylation (PARylation) of substrates in regulating gene transcription. We show here that HIV-1 transcriptional activationalso requires PARP1 activity. Because efficient HIV-1 transactivation is knowntodependontheELL2-containing super elongation complex (SEC), we investigated the functional relationship between PARP1 and ELL2-SEC in HIV-1 transcriptional control. We show that PARP1 elevates ELL2 protein levels to form more ELL2-SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…Together with the finding on ZL0580-induced reduction of CDK9 binding to Tat (Figure 6C), these data help explain why ZL0580 reduces RNAPII activation ( Figure 6G). Our data also imply that ZL0580 inhibits ELL2 by reducing its protein stability ( Figure 6, E and F), consistent with recent studies reporting that posttranslational ubiquitination and proteasome degradation (mediated by Siah1, an E3 ligase) is a major mechanism for cellular regulation of ELL2 (43,44). In addition, we revealed that ZL0580 induces ELL2 or presence of ZL0580 or ZL0454.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Together with the finding on ZL0580-induced reduction of CDK9 binding to Tat (Figure 6C), these data help explain why ZL0580 reduces RNAPII activation ( Figure 6G). Our data also imply that ZL0580 inhibits ELL2 by reducing its protein stability ( Figure 6, E and F), consistent with recent studies reporting that posttranslational ubiquitination and proteasome degradation (mediated by Siah1, an E3 ligase) is a major mechanism for cellular regulation of ELL2 (43,44). In addition, we revealed that ZL0580 induces ELL2 or presence of ZL0580 or ZL0454.…”
Section: Discussionsupporting
confidence: 92%
“…These data together indicate that downregulation of ELL2 may represent another mechanism by which ZL0580 engages BRD4 to suppress HIV in addition to the established role of BRD4 in competing with Tat for cellular CDK9 as described earlier. Our data also raised several interesting issues that have not yet been addressed: (a) whether ELL2 deficiency plays a role in SEC assembly at the HIV promoter; (b) whether E3 ligases, for example Siah1 (43,44), mediate ELL2 ubiquitination and destabilization after ZL0580 treatment; and (c) how BRD4 engages cellular mechanisms (e.g., E3 ligase) to destabilize ELL2 and thereby regulate HIV transcription. Addressing these gaps, especially the mechanistic connection between BRD4 and ELL2, in future research will not only improve our understanding of mechanisms of action (MoA) for ZL0580, but also provide insights into HIV proviral regulation and latency.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another important example is PARP1. Whereas an older study cited in the NCBI database (33) proposed its function as an HIV transcriptional repressor via competition with Tat for binding TAR, a recent study (44) provided strong evidence that HIV transcriptional activation requires PARP1 activity. Different functional domains of PARP1 (DNA-binding and catalytic, respectively), have been implicated in these two studies.…”
Section: Secondary Mechanisms Of Action Of Hdaci and Hiv Latencymentioning
confidence: 99%
“…Besides SEC, ELL also associates with EAF1, KIAA0947 (aka ICE1), and NARG2 (aka ICE2) to form Little Elongation Complex (LEC) that functions in regulating small nuclear RNA gene transcription by Pol II as well as in the recruitment of TFIIH during transcription-coupled DNA repair (11)(12)(13). Although mechanisms of ELL2 degradation by the E3 ubiquitin ligase, Siah1, have been described by two earlier studies (14,15), regulation of ELL function through its stabilization is completely unknown. In this regard, we were intrigued by the strong association of Deleted in Breast Cancer 1 (DBC1) in our ELL.com mass spectrometric analysis (2) and SI Appendix, Fig.…”
mentioning
confidence: 99%